Evaluating intermittent irrigation strategies for rice production to mitigate greenhouse gas emissions and preserve yields in contrasting environments - Loaiza, Sandra; Verchot, Louis; Costa, Ciniro; Bolaños, Isabel; Garces, Gabriel; Puentes, Oscar; Ardila, Jorge; Trujillo, Catalina; Chirinda, Ngonidzashe (Frontiers in Agronomy, 2025)
Intermittent irrigation is widely recognized for potentially reducing global methane (CH4) emissions from flooded rice systems. In many regions, including parts of Asia and Latin America, applying inorganic fertilizers and choosing fertilizer types are vital strategies to mitigate nitrous oxide (N2O) emissions by controlling soil moisture. These practices have been increasingly adopted as part of sustainable rice cultivation methods aimed at reducing greenhouse gas emissions. However, despite their effectiveness, adoption of such practices remains limited in several rice-growing areas, particularly in developing regions. Consequently, the comprehensive effects of intermittent irrigation on CH4 and N2O emissions and rice grain yield require further investigation to understand their global implications fully. The objectives of this study were to examine the differential impacts of water management strategies, specifically intermittent irrigation versus flooded irrigation, on greenhouse gas emissions in two rice-growing regions in Colombia: Tolima and Casanare. Our analysis includes methane (CH4) and nitrous oxide (N2O) emissions, global warming potential (GWP), and crop yields using randomized block designs for commercial rice varieties. The results demonstrate that transitioning from flooding to intermittent irrigation has significant environmental benefits. In particular, such a switch enables a drastic reduction in CH4 emissions, which were reduced by almost 100% in Tolima and Casanare. Notably, a 54% to 78% reduction in N2O emissions is observed in Tolima, 6% to 46% in rainfed systems, and 100% in irrigated systems when soil moisture was maintained near field capacity during fertilization in Casanare. Crop yield shows no significant differences in both regions. Intermittent irrigation reduced GWP by 62% to 85% in Tolima, and by 14% to 62% in rainfed systems, and 100% in irrigated systems in Casanare. This study concludes that shifting from flooded to intermittent irrigation minimizes rice production’s GWP and greenhouse gas emissions while preserving yields. Optimized water management contributes to reduced N2O emissions.